DRIVEN POLYSTRONG REINFORCED CONCRETE PILES AND NEW DESIGN OF PILE CAPS - I. I. Bekbasarov; G. I. Isakov (Наука и техника)
The paper presents constructional and technological features for manufacturing driven piles with variable strength of pile shaft. Economical efficiency of their production has been shown in the paper. The paper provides a pile cap design that ensures perception of hammer impacts with the help of lateral edges of the pile cap. Driven reinforced concrete piles which are manufactured from three shaft sections having various strength have been proposed in the paper. Material strength (concrete grade and diameter of bars) and length of shaft sections are given on a case by case basis in accordance with nature and rate of stresses in piles during their driving process. Manufacturing of polystrong piles provides an opportunity to select them for a particular construction site with due account of their preservation during driving process.A pile cap has been developed that as opposed to existing analogous designs makes it possible to transmit impact efforts from a hammer to the pile through lateral surface of its head part. The pile cap provides the possibility to increase an area for perception of hammer impact efforts by the pile and in doing so it is possible significantly to reduce a damage risk and destruction of pile concrete during its driving. Application of polystrong piles and their driving with the help of new pile cap are considered as a basis for defect-free and resource-saving technology for pile foundations in the construction.